ANALYSIS OF THEORETICAL AND METHODOLOGICAL BASIS OF DEVELOPMENT OF AXIOLOGICAL ATTITUDE OF YOUTH TO DEMOCRATIC REFORMS (Scientific journal of the Fergana State University, 2023)
This article analyzes the theoretical and methodological foundations of the development of the axiological attitude of young people to democratic reforms in our country, the study of values by scientists and the problems. Also, it is stated that the great thinkers, who played an important role in the history of Eastern culture, studied the issue of values from a scientific point of view, and that the improvement of the mechanisms of developing axiological attitudes of young people to democratic reforms is of urgent importance.